PENGARUH PENERIMAAN PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (STUDI KASUS PADA BADAN PENDAPATAN DAERAH KOTA BEKASI) - Nauli, Halberry Tania; Ismail, Marthinus; Susanti, Mila (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The focus of the knowledge analysis will be Regional Original Income influenced by Hotel and Restaurant Taxes in Bekasi City. This research analyzes the 2018–2023 hotel and restaurant taxes using the Classic Assumption Test, t test, F test and determination. In this case, the t test shows that there is quite a large influence between Hotel Tax 0.002 < 0.05 Restaurant Tax, and the F test shows that Hotel Tax and Restaurant Tax both help the research show that Hotel and Restaurant Tax increases regional income in Bekasi City, and these two taxes have a significant effect on the Regional Original Income of Bekasi City with a significance limit of 0.004 < 0.05. The conclusion is that these two taxes affect Regional Original Income simultaneously.